FEM Simulation on Stencil Bending Due to Squeegee Load during Solder Paste Stencil Printing Process - Azlee, Muhammad Haziq (Universiti Sains Malaysia, 2021)
In the assembly of the printed circuit board, the squeegee moves in one direction with the application of load on the squeegee. This will result from the squeegee deflect the stencil and Printed Circuit Board (PCB) throughout the stencil printing process. This loading creates micro-bending on the stencil and will affect the solder paste volume that is deposited. FEM will be used to study the effect of squeegee load on the stencil bending. The parameter such as the material of the squeegee, the material of the stencil, the thickness of the squeegee and the thickness of stencil is the main criteria for the result of the simulation for the bending of the stencil and the PCB. The higher the tensile strength of the material for the stencil, the lower the deflection of the stencil. In this study, material such as Alloy Steel, AISI 4340 Steel, Annealed and AISI 316 Stainless Steel Sheet was used as they are widely used in the industry. In this study also, AISI 321 Annealed Stainless Steel, AISI 4340 Steel, Normalized and Alloy Steel was used as they are widely used in industry. The material of the Printed Circuit Board (PCB) is Epoxy, Unfilled was used as it is widely used in the industry. The higher the tensile strength of the squeegee, the higher the deflection of the stencil and the Printed Circuit Board (PCB). The higher the thickness of the Printed Circuit Board (PCB), the lower the deflection of the stencil. The SOLIDWORKS 2020 2-D Static Simulation approach is used to study the deflection of the stencil due to the squeegee. This simulation is carried out at three different types of material for the stencil and squeegee.